The dangers of castor oil tea in neonates in rural Haiti: A case report - Jean Baptiste, Wilhermine; Casseus, Michelucia; Dev, Alka; Joseph, Patrice; Wright, Peter F. (Frontiers in Pediatrics, 2023)
During a two-year period, eight cases of a distinct illness were seen among 1424 neonates admitted to a newly established neonatal care unit in southern Haiti. Five cases were fatal. In each case, the illness was associated with ingestion of teas that included castor oil, known as lok in Haitian Creole. The definitive diagnosis was established by the presence of a dark, oily substance in drainage from the nasogastric tubes and by subsequent admission on direct questioning of the caregivers that the infant had been given lok. The castor oil tea was given in three cases in the immediate neonatal period where its use is attributed to encouraging passage of meconium. The five remaining cases were between 15-30 days of life when they were given lok shortly before admission to the neonatal unit. All infants were term infants with no identified risks at birth. As nasogastric tubes are not routinely placed in sick neonates and parents did not volunteer information about lok administration, the practice may be more widespread than that recorded here. Although our data is confined to observations in Haiti, the use of traditional medicines is widespread globally. Attention must be drawn to the potential toxicity of such preparations and means found to ban their use in neonates.